Decomposition of a Potassium-Based Supersaturated Zincate Solution in Electrolytes with Reduced Zinc Solubility. (25th November 2020) - Smejkal, Jan; Chladil, Ladislav
Abstract : The decomposition rate of supersaturated zincate electrolytes based on 6 mol·dm -3 KOH was measured and the effect of additives used for reducing zincate solubility (KF, K2 CO3, K3 PO4 ) was evaluated. The electrolytes were studied after being aged for 5 years at room temperature. Powder morphology was obtained as a result of recrystallization processes were evaluated. Results indicate that the presence of 1 mol·dm -3 PO4 3- ions reduced the speed of decomposition to less than half. A study of ZnO recrystallization revealed the changes in particle sizes for all additives. Despite the long time of recrystallization processes, ZnO particles grew to different sizes depending on the type of low solubility electrolyte (LSE) used. While the presence of PO4 3- and F - ions promote the particle growth in all directions and thus influence both particle lengths and widths. The presence of carbonate ions CO3 2- reduce the particle sizes and thus could contribute to the growth of a larger active area of electrodes after long-term aging.